ANALYSIS OF VERBAL AGRESSION THROUGH DISCURSIVE, PRAGMATIC AND CORPUS APPROACHES (Scientific journal of the Fergana State University, 2025)
The article focuses on the study of aggression in communication using pragmatic, discursive, and corpus approaches. Aggression in communication is viewed as a multifaceted phenomenon, including various forms of expression such as direct, hidden, and pragmatic aggression. Pragmatic analysis focuses on the goals and strategies employed by communication participants, while discursive analysis examines aggression as a construct formed in language. The corpus approach allows for a quantitative assessment of the frequency of aggressive statements in different types of texts, highlighting patterns of their usage. The study's results show that aggression is widespread in digital communications, especially in the context of anonymity, and influences the dynamics of interpersonal and intergroup interactions. The article emphasizes the importance of a comprehensive approach in studying aggression, which enables a deeper understanding of its social and psychological aspects.